Computational Calculation and Molecular Docking of Thymol and O-Benzoyl Thymol as Inhibitor TYK2 Enzyme - Maahury, Mirella Fonda; Baharudin, Muhammad Daswar A.; Zainul, Rahadian; Khalid, Ahmad Khudzairi; Jakmola, Vikash; Rebezov, Maksim (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Thymol is the active ingredient in plants from Thymus vulgaris (thymus). The calculations and molecular docking have been done computationally for the thymol and o-benzoyl thymol. This computational calculation aims to obtain a stable structure and electronic properties of thymol and o-benzoyl thymol. The computational analysis used DFT for geometry optimization in the gas phase using B3LYP functional and 3-211G(d) as the basis set. The optimized structure of thymol and o-benzoyl thymol is not planar. The functional benzoyl decreases the bond length, increases the bond angle, and turns the dihedral. The electronic properties, such as atomic charge and density of HOMO-LUMO, show the difference between the two molecules. The optimized structure of thymol and o-benzoyl thymol is used for molecular docking with the TYK2 enzyme (tyrosine kinase). In this research, thymol and o-benzoyl thymol can inhibit TYK2 enzyme with the bond affinity is about -5.909 kcal/mol and -7.456 kcal/mol, respectively, for thymol o-benzoyl thymol. The primary molecular interaction is hydrophobic.